On qualitative smoothness of kernel density estimates1 - Mammen, Enno (Statistics, 1995)
In this paper we give asymptotic expansions for the expected number of local extremes and inflection points of kernel density estimates. We argue that these numbers can be used as an indicator for the “qualitative” smoothness of the density estimate.